Effectiveness of Aloe Vera Extract (Aloe vera L.) Against Colletotrichum capsici Fungi and Its Use as a Learning Media - Tiara Elza; I Nengah Kundera; I Made Budiarsa (CV. Dharma Samakta Edukhatulistiwa, 2024)
This study aims to determine the effectiveness of aloe vera extract (Aloe vera L.) against Colletotrichum capsici fungus and determine the optimal concentration of aloe vera extract that effectively inhibits the growth of Colletotrichum capsici fungus and is used as a learning medium. This study used a laboratory experiment method using a Complete Random Design (RAL) with 5 treatments and 4 replicates. The treatment consisted of a concentration of 0% as a negative control, a concentration of aloe vera extract of 25%, 50%, 75% and 100%. The observed parameter is the diameter of the formed inhibition zone. The results of the study used Variant Analysis (ANOVA) and continued with the smallest real difference (BNT) test. The results showed that the administration of aloe vera extract (Aloe vera L.) could inhibit the growth of Colletotrichum capsici fungus at a maximum concentration of 100%. The higher the concentration of aloe vera extract, the higher its ability to inhibit the growth of Colletotrichum capsici fungus. The results of this study are feasible to be implemented in the form of a digital flipbook as a learning medium with a feasibility of 83.2%.